Joint Studies of Spin Frustration Induced by Doping Small ZnSe Nanoparticles with Fe Atoms. Issue 1 (25th November 2022) - Gutsev, Lavrenty G.; Bindra, Jasleen K.; Strouse, Geoffrey F.; Aldoshin, Sergey M.; Gutsev, Gennady L.
Abstract: As a 1.8 nm ZnSe nanocrystal is progressively doped with 1%, 5%, and 10% Fe, it shows a progressive change in its magnetic properties from a superparamagnetic FM‐dominated exchange type to an onset of AFM exchange with evidence of spin frustration. Magnetization measurements allow to obtain exchange coupling constants that are compared to the results of a Broken‐Symmetry Density Functional Theory (BS‐DFT) model of a doped (ZnSe)34 cluster. DFT shows a capability to reproduce the experimental pattern of the increasing influence of AFM exchange as doping concentration increases. The material phase segregates at the edges where strained rhombic surface sites are the preferred doping sites of iron. Large concentrations of iron leads to the formation of Fe clusters and complex exchange patterns that result in spin frustration in some iron trimers but none in the others. The spin frustration of these complex systems by assuming mirror symmetry of the sites when fitting by using BS‐DFT formalism is classified and analyzed. While some individual J constants obtained have significant errors, the averaged exchange constants are generally in good agreement with our experimental data. Abstract : Experimental measurements of 1.8 nm ZnSe nanocrystals doped with up to 10% iron indicated a gradual shift from FM‐dominated SPM behavior to AFM behavior. This behavior is analyzed with Broken‐Symmetry DFT which demonstrates that a phase segregation of the material leads to AFM–FM competition and geometrical spin frustration in the lattice.